Information security applications 11th International Workshop, WISA 2010, Jeju Island, Korea, August 24-26, 2010, Revised selected papers - WISA (Workshop : Information security) 2010 Cheju-do, Korea); Chung, Yongwha; Yung, Moti.; SpringerLink (Online service). (Berlin Springer, 2011)
This book constitutes the refereed proceedings of the 11th International Workshop on Information Security Applications, WISA 2010, held in Jeju Island, Korea, in August 2010. The 25 revised full papers presented were carefully reviewed and selected from 107 submissions. The papers are organized in topical sections on cryptosystem, implementation, mobile security/secure coding, attack, biometrics, and secure protocol.
Electronic reproduction.
Keywords: Computer security -- Congresses; Computers -- Access control -- Congresses; Data encryption (Computer science) -- Congresses; Electronic books